VD_FINDINFO ML / 2011 / 193 vom 9. September 2011 - VD Tribunal cantonal (2011)
ACTION EN CONSTATATION, MEILLEURE FORTUNE, EXCEPTIONMOYEN DE DÉFENSE, MOYEN DE DROIT | 265a al. 1 LP, 265a al. 4 LP, 63 CPC (CH)